Manajemen Stress Guru Sekolah Luar Biasa Untuk Membimbing Anak Berkebutuhan Khusus di SLB Purba Adhi Suta Purbalingga - Ermit Three; Muh. Hanif (Journal on Education, 2024)
The focus of this research is to find out how Lazarus and Folkman's theory is applied to stress management in special schools in guiding children with special needs at SLB Purba Adhi Sita Purbalingga. Another focus is to find out how the mindfulness program popularized by Kabat-Zinn can be developed to help students deal with stress related to their special needs and the third is, How self-efficiency theory can be used to increase children's self-confidence. with special needs at SLB Purba Adhi Suta Purbalingga about their ability to deal with stressful situations, as well as how increasing self-efficacy can help them become more confident and more effective in dealing with stress related to their special needs. By implementing appropriate coping strategies in accordance with Lazarus and Folkman's theory, teachers can guide students in achieving learning goals effectively and efficiently. In this research, the interview method is the right step to obtain answers regarding the research focus. This research is a qualitative descriptive study. The appropriate data collection method is interviews that will be conducted with the principal, head of student affairs, guidance and counseling teachers, subject teachers and homeroom teachers who have more meeting time with students at SLB Purba Adhi Sita Purbalingga. The three theories above can also be applied to public school management, if obstacles are found in the learning process. The results of this research will certainly add general insight to all educational institutions in Indonesia, both SLB Purba Adhi Sita Purbalingga and state schools.